The Brain Waves During Reaching Tasks in People With Subacute Low Back Pain: A Cross-Sectional Study - Hsin-Hui Hsu; Yea-Ru Yang; Li-Wei Chou; Yung-Cheng Huang; Ray-Yau Wang (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Subacute low back pain (sLBP) is a critical transitional phase between acute and chronic stages and is key in determining the progression to chronic pain. While persistent pain has been linked to changes in brain activity, studies have focused mainly on acute and chronic phases, leaving neural changes during the subacute phase—especially during movement—under-researched. This cross-sectional study aimed to investigate changes in brain activity and the impact of pain intensity in individuals with sLBP during rest and reaching movements. Using a 28-electrode EEG, we measured motor-related brain waves, including theta, alpha, beta, and gamma oscillations. Transitioning from rest to movement phases resulted in significant reductions (>80%) in mean power across all frequency bands, indicating dynamic brain activation in response to movement. Furthermore, pain intensity was significantly correlated with brain wave activity. During rest, pain intensity was positively correlated with alpha oscillation activity in the central brain area (r = 0.40, p <0.05). In contrast, during movement, pain intensity was negatively correlated with changes in brain activity (r = −0.36 to −0.40, p <0.05). These findings suggest that pain influences brain activity differently during rest and movement, underscoring the impact of pain levels on neural networks related to the sensorimotor system in sLBP and highlighting the importance of understanding neural changes during this critical transitional phase.